KARAKTERISTIK DAN SEBARAN SITUS KUBUR TEMPAYAN DI ASIA DARATAN DAN KEPULAUAN, KAWASAN ASIA TENGGARA - Fadhila Arifin Aziz (Berkala Arkeologi, 1998)
Most of the urn/ pottery jar burial sites each have special characteristics, both in the way the body is placed in the jars, the materials used, the shape and decoration, the layout and distribution in the unit location, and so on. At some sites, these urn burials were found along with burials without containers, and some were even side by side with burials from later periods. This paper is an overview of the characteristics of the urn burials and the distribution of several sites in the Southeast Asia region.